Occurrence and characterization of cyst nematode species (Globodera spp.) associated with potato crops in Colombia - Vallejo, Daniela; Rojas, Diego A.; Martinez, John A.; Marchant, Sergio; Holguin, Claudia M.; Pérez, Olga Y. (Cold Sprimg Harbor Laboratory (CSH), 2025)
Potato cyst nematodes (PCN) from the genus Globodera spp. cause major losses in potato (Solanum tuberosum) industry worldwide. Despite their importance, at present little is known about the status of this plant pathogen in cultivated potatoes in Colombia. In this study, a total of 589 samples collected from 75 geographic localities from nine potato producing departments of Colombia were assayed for the presence of potato cyst nematodes. Fifty-seven percent of samples tested positive for PCN. All populations but one were identified as Globodera pallida, with conspicuous morphometric variation found among populations. Based on phylogenetic analysis of the internal transcribed spacer region (ITS1-5.8S-ITS2) of the rRNA gene and D2-D3 expansion segments of the 28S rRNA gene, G. pallida from Colombia formed a monophyletic group closely related to Peruvian populations, with the lowest average number of nucleotide substitutions per site (Dxy= 0.002) and net nucleotide substitutions per site (Da= 0.001), when compared to G. pallida populations from South, North America and Europe. A single sample formed a well-supported subclade along with G. rostochiensis and G. tabacum from Japan, USA and Argentina. To our knowledge this is the first comprehensive survey of Globodera populations from Colombia that includes morphological and genetic data. Our findings on species diversity and phylogenetic relationships of Globodera populations from Colombia may help elucidate the status and distribution of Globodera species, and lead to the development of accurate management strategies for the potato cyst nematodes.